Urgency of The Position of District Election Supervisory Body in The Resolution of Disputes Between Participants in The Regional Head Election in Indonesia - Muhammad Yusrizal Adi Syaputra (Jurnal Penelitian Hukum De Jure, 2022)
The ad hoc position of the District Election supervisory body will have an impact on actions to carry out the functions and duties of the District Election supervisory body during the election of regional heads. This study aims to determine the urgency of the position of the District Election supervisory body in the formation of effective supervision in the Pilkada and to find out the Mechanism of Dispute Resolution between Election Participants by the District Election supervisory body in the election of regional heads. This study uses a normative juridical research method, with secondary data and a conceptual approach. The data were analyzed qualitatively. The result of the first study is that the decision of the Election supervisory body an ad hoc institution is binding but still limited and not final because the aggrieved party can file a lawsuit to the State Administrative High Court. The mechanism for resolving disputes between participants in the Pilkada organizers by the District Election supervisory body is regulated technically through Election supervisory body Number 2 of 2020. Disputes between participants are carried out on the principle of the quick and simple, same-day to achieve legal certainty and benefit in regional head elections.